1985
DOI: 10.1002/pd.1970050112
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of pyruvate carboxylase deficiency

Abstract: Prenatal diagnosis of pyruvate carboxylase (PC) deficiency was performed in a family at risk for the acute neonatal form of this disease which manifests secondary citrullinemia. The diagnosis of an affected child was confirmed by enzyme assay and 3H-biotin labelling of proteins in cultured fetal skin fibroblasts. Sufficient amniocytes were cultured in 3-4 weeks for enzyme analysis in two centres. Citrulline concentration in amniotic fluid (AF) was normal in the affected fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Table 1 compares the clinical features presented by the two male siblings described in this study (Cases 1 and 2) relative to normal and Type A PC deficient subjects. The biochemical and molecular data for these two siblings has previously been reported [Robinson et al, 1984;Robinson et al, 1985]. Case 2 is an affected fetus and the male sibling of Case 1.…”
Section: Rna Extraction and Cdna Preparationmentioning
confidence: 81%
See 1 more Smart Citation
“…Table 1 compares the clinical features presented by the two male siblings described in this study (Cases 1 and 2) relative to normal and Type A PC deficient subjects. The biochemical and molecular data for these two siblings has previously been reported [Robinson et al, 1984;Robinson et al, 1985]. Case 2 is an affected fetus and the male sibling of Case 1.…”
Section: Rna Extraction and Cdna Preparationmentioning
confidence: 81%
“…Diagnosis was based on a PC enzyme assay [Robinson et al, 1985] modified from the method of Utter and Keech [Utter and Keech, 1963] [Robinson et al, 1987;Robinson et al, 1983;Robinson et al, 1984]. The results are presented in Table 1.…”
Section: Materials and Methods Patient Samplesmentioning
confidence: 99%
“…However, we have no evidence to support this hypothesis. In fact, Robinson et al (17) have shown evidence for brain involvement during fetal development in a PC-deficient patient.…”
Section: Discussionmentioning
confidence: 99%
“…hyperammonemia (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Essentially all these patients died within the first 4 mo of life.…”
mentioning
confidence: 99%
“…Also, a benign variant has been reported in a seven-year-old girl whose motor and mental abilities remained largely intact (Van Coster et al, 1991). Marsac et al (1982) reported the successful prenatal diagnosis of PC deficiency using a radiometric assay in cultured amniocytes, as have others (Robinson et al, 1985).…”
Section: Introductionmentioning
confidence: 98%